Correlation between excited d-orbital electron lifetime in polaron dynamics and coloration of WO 3 upon ultraviolet exposure - Lee, Young Ahn; Han, Seung Ik; Rhee, Hanju; Seo, Hyungtak (Applied Surface Science, 2018)
Polarons have been suggested to explain the mechanism of the coloration of WO 3 induced by UV light. However, despite the many experimental results that support small polarons as a key mechanism, direct observation of the carrier dynamics of polarons have yet to be reported. Here, we investigate the correlation between the electronic structure and the coloration of WO 3 upon exposure to UV light in 5% H 2 /N 2 gas and, more importantly, reveal photon-induced excited d-electron generation/relaxation via the W 5+ oxidation state. The WO 3 is fabricated by radio-frequency magnetron sputtering. X-ray diffraction patterns show that prepared WO 3 is amorphous. Optical bandgap of 3.1 eV is measured by UV–vis before and after UV light. The results of Fourier transform infrared and Raman exhibit pristine WO 3 is formed with surface H 2 O. The colored WO 3 shows reduced state of W 5+ state (34.3 eV) by using X-ray photoelectron spectroscopy. The valence band maximum of WO 3 after UV light in H 2 is shifted from mid gap to shallow donor by using ultraviolet photoelectron spectroscopy. During the exploration of the carrier dynamics, pump (700 nm)–probe (1000 nm) spectroscopy at the femtosecond scale was used. The results indicated that electron-phonon relaxation of UV-irradiated WO 3 , which is the origin of the polaron-induced local surface plasmonic effect, is dominant, resulting in slow decay (within a few picoseconds); in contrast, pristine WO 3 shows fast decay (less than a picosecond). Accordingly, the long photoinduced carrier relaxation is ascribed to the prolonged hot-carrier lifetime in reduced oxides resulting in a greater number of free d-electrons and, therefore, more interactions with the W 5+ sub-gap states.
Keywords: Direct observations; Electron-phonon relaxation; Fourier transform infra reds; Photochromic; Pump probe; Radio frequency magnetron sputtering; Ultraviolet exposure; Valence-band maximums; Hydrogen; Photochromic; Polaron; Pump-probe; WO 3